2021
DOI: 10.3390/nursrep11030054
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Using Personal Protective Equipment and Headache among Healthcare Workers in Saudi Arabia Hospitals during the COVID-19 Pandemic

Abstract: It is mandatory that healthcare workers wear personal protective equipment (PPE) while caring for COVID-19 patients. Studies have shown that wearing PPE for a prolonged time may lead to symptoms of physical discomfort including headache. The aim of this study is to assess the prevalence and association between prolonged use of PPE and headaches. This was a cross-sectional study. A convenience sample of healthcare workers who worked with COVID-19 patients in clinical settings was recruited. The data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Therefore, this condition could aggravate a pre-existing cervical disorder and exacerbate the headache associated with protective masks. 24,25 No statistically significant data on the presence of joint noise was found in our study. Indeed, masks seem to not cause joint damage because both the force application quantity and duration are not enough high to create articular injuries.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Therefore, this condition could aggravate a pre-existing cervical disorder and exacerbate the headache associated with protective masks. 24,25 No statistically significant data on the presence of joint noise was found in our study. Indeed, masks seem to not cause joint damage because both the force application quantity and duration are not enough high to create articular injuries.…”
Section: Discussioncontrasting
confidence: 58%
“…It might be assumed that in people who wear the mask with the elastic bands behind the neck, this kind of headache could be caused by the pressure of the elastic on the neck or back head superficial nerves. Therefore, this condition could aggravate a pre‐existing cervical disorder and exacerbate the headache associated with protective masks 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Saudi Arabian survey of 1060 healthcare workers who worked at a hospital during the COVID-19 pandemic reported that the risk of headache increased with the increasing duration of PPE use in people with and without pre-existing headaches. Moreover, the use of PPE also provoked nausea, vomiting, sensitivity to light, sound, and motion, and throat discomfort 66 . In a study on burnout among healthcare workers who worked in a high-risk region in China during the COVID-19 pandemic, physical symptoms and acute stress were significantly correlated with emotional exhaustion and disengagement (cynicism), indicating burnout 67 , and a study in 2001 on the relationship between workload and burnout reported that excessive workload leads to emotional exhaustion, which in turn leads to disengagement (cynicism), which can trigger physical symptoms 68 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the partial pressures of carbon dioxide and oxygen were not evaluated in this study. Cervicogenic headaches, that is a subtype of headache describing headaches arising from the neck, are usually associated with primary cervical disease (17)(18)(19)(20)(21). It might be assumed that in people who wear the mask with the elastic bands behind the neck, this kind of headache could be caused by the pressure of the elastic on the neck or back head super cial nerves, therefore this condition could aggravate a pre-existing cervical disorder and exacerbate the headache associated with protective masks.…”
Section: Discussionmentioning
confidence: 99%